BRAF and MEK Inhibition Variably Affect GD2-specific Chimeric Antigen Receptor (CAR) T-Cell Function In Vitro. Issue 1 (January 2015) - Gargett, Tessa; Fraser, Cara K.; Dotti, Gianpietro; Yvon, Eric S.; Brown, Michael P.
Abstract : Cancer immunotherapy has long been used in the treatment of metastatic melanoma, and an anti-CTLA-4 monoclonal antibody treatment has recently been approved by the US Food and Drug Administration. Targeted therapies such as small molecule kinase inhibitors targeting deregulated mitogen-activated protein kinase (MAPK) signaling have markedly improved melanoma control in up to 50% of metastatic disease patients and have likewise been recently approved. Combination therapies for melanoma have been proposed as a way to exploit the high-level but short-term responses associated with kinase inhibitor therapies and the low-level but longer-term responses associated with immunotherapy. Cancer immunotherapy now includes adoptive transfer of autologous tumor-specific chimeric antigen receptor (CAR) T cells and this mode of therapy is a candidate for combination with small molecule drugs. This paper describes CART cells that target GD2-expressing melanoma cells and investigates the effects of approved MAPK pathway-targeted therapies for melanoma [vemurafenib (Vem), dabrafenib (Dab), and trametinib (Tram)] on the viability, activation, proliferation, and cytotoxic T lymphocyte activity of these CAR T cells, as well as on normal peripheral blood mononuclear cells. We report that, although all these drugs lead to inhibition of stimulated T cells at high concentrations in vitro, only Vem inhibited T cells at concentrations equivalent to reported plasma concentrations in treated patients. Although the combination of Dab and Tram also resulted in inhibition of T-cell effector functions at some therapeutic concentrations, Dab itself had little adverse effect on CAR T-cell function. These findings may have implications for novel therapeutic combinations of adoptive CAR T-cell immunotherapy and MAPK pathway inhibitors. Abstract : Supplemental Digital Content is available in the text.